2015
DOI: 10.1021/acs.jctc.5b00588
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Empirical Models versus High-Accuracy Ab Initio Methods for Nucleobase Stacking: Evaluating the Importance of Charge Penetration

Abstract: Molecular mechanics (MM) force field models have been demonstrated to have difficulty reproducing certain potential energy surfaces of π-stacked complexes. Here, we examine the performance of the AMBER and CHARMM models relative to high-quality ab initio data across systematic helical parameter scans and typical B-DNA geometries for π-stacking energies of nucleobase dimers. These force fields perform best for typical B-DNA geometries (mean absolute error < 1 kcal mol(-1)), whereas errors typically approach ∼2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 57 publications
0
63
0
Order By: Relevance
“…SAPT2+), a previously published nucleobase stacking interaction energy database 21 with SAPT0 data was used in the validations. The QM energy decomposition was obtained using the SAPT0/jun-cc-pVDZ method.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…SAPT2+), a previously published nucleobase stacking interaction energy database 21 with SAPT0 data was used in the validations. The QM energy decomposition was obtained using the SAPT0/jun-cc-pVDZ method.…”
Section: Resultsmentioning
confidence: 99%
“…With 28 pairs of vdW parameters for 9 chemical elements, we are able to reproduce vdW interaction energy for all dimers in this database with a RMSE of 1.68 kcal/mol (0.84 kcal/mol if within 90–110% of the equilibrium distances). Subsequently, the accuracy and transferability of the vdW2016 potential were validated by comparing to the SAPT0 energy of an additional set of stacked nucleobase 42 and newly generated cross-interacting dimers (S36x7). As a result, the vdW2016 potential yields strong correlations with R 2 of 0.983 for all base pairs and 0.994 for 259 heterodimers compared to the SAPT0 energy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parker and Sherrill recently showed that without an explicit accounting for charge penetration, force fields struggle to accurately reproduce the ab initio electrostatic energies of these interactions. 8 For instance in an AC:GT base step, the mean absolute errors (MAE) of the AMBER 31, 32 and CHARMM 33 force fields relative to the SAPT electrostatic energy were over 20 kcal/mol. Likewise, we find that AMOEBA without charge penetration gives an electrostatic energy MAE over 20 kcal/mol as well.…”
Section: Test Case: Nucleic Acid Base Stackingmentioning
confidence: 99%
“…Parker and Sherrill have recently shown that without charge penetration, it is difficult, if not impossible to accurately capture the electrostatics of interacting nucleobases. 8 These considerations show that if AMOEBA is to be successful in accurately modeling biologically relevant interactions such as nucleic acid folding or ligand binding, we must account for the short-range electrostatics of charge penetration.…”
Section: Introductionmentioning
confidence: 99%